2016
DOI: 10.1590/1984-70332016v16n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis applied to the G+GE matrix via REML/BLUP for multi-environment data

Abstract: -The genotype x environment interaction is frequently observed in many crops and studies on environmental stratification and genotype adaptability have been proposed to understand it. The aim of this study was to carry out factor analysis in data from multi-environment experiments by the mixed model approach (REML/BLUP). Instead of adjusted phenotypic means, a matrix containing the genotypic effects added to the effects of the genotype x environment interaction (G+GE) was used, predicted via REML/BLUP in joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Other authors reported similar results, reinforcing that this method leads to a refinement of cultivar selection, as well as having the advantage of providing results on the proper measurement scale of the trait (Carbonell et al, 2007). The GE interaction is one of the great challenges for breeders, particularly in the evaluation stages of genotypes for recommendation for producers, since the experiments are carried out at different locations and in different years and growing seasons (Peixouto et al, 2016).…”
Section: Traits With H Gmentioning
confidence: 99%
“…Other authors reported similar results, reinforcing that this method leads to a refinement of cultivar selection, as well as having the advantage of providing results on the proper measurement scale of the trait (Carbonell et al, 2007). The GE interaction is one of the great challenges for breeders, particularly in the evaluation stages of genotypes for recommendation for producers, since the experiments are carried out at different locations and in different years and growing seasons (Peixouto et al, 2016).…”
Section: Traits With H Gmentioning
confidence: 99%
“…The mixed-model methods, such as the restricted maximum likelihood/best linear unbiased prediction (REML/BLUP), enable the estimation of variance components and the prediction of genetic values free of environmental effects (Peixouto et al, 2016). The following methods may be used: the harmonic mean of genotypic values (HMGV), in order to infer mean and stability; the relative performance of predicted genotypic values (RPGV), to analyze the genotypic adaptability and the mean yield; and the harmonic mean of the relative performance of predicted genotypic values (HMRPGV), to identify highlyproductive, adapted, and stable genotypes (Gomez et al, 2014;Costa et al, 2015;Spinelli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of G × E, the two-stage method tends to fit easily compared to traditional methods, such as the factor-analytic method. e factor-analytic method tries to simplify a complex covariance structure and, in some cases, for example, in the case of G × E, difficulty in reaching convergence [32].…”
Section: A1 A2mentioning
confidence: 99%